Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.20452/pamw.16421
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated thrombosis: comparison of characteristics, treatment, and outcomes in oncological and non-oncological patients followed by Pulmonary Embolism Response Team

Abstract: This study is a retrospective analysis of consecutive patients with venous thromboembolism (VTE) treated by the Pulmonary Embolism Response Team CELZAT (PERT-CELZAT) that compares the clinical characteristics, outcomes, and mortality of patients with and without cancer. It shows that patients with cancer can be successfully treated for pulmonary embolism (PE) with their in-hospital outcomes and mortality rate at the same level as patients without cancer. The study postulates that patients with PE, especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Advanced oncological disease is reported to be the most common cause of death in the posthospital period [30][31][32]. A recent study indicated three times higher mortality during 12 months after PE diagnosis as compared to non-oncological patients [33]. There was one case of ischemic stroke after the CDMT procedure in our cohort.…”
Section: Safety Outcomesmentioning
confidence: 49%
“…Advanced oncological disease is reported to be the most common cause of death in the posthospital period [30][31][32]. A recent study indicated three times higher mortality during 12 months after PE diagnosis as compared to non-oncological patients [33]. There was one case of ischemic stroke after the CDMT procedure in our cohort.…”
Section: Safety Outcomesmentioning
confidence: 49%
“…This might be associated with a lack of standardized algorithms to select patients for advanced PE therapies and variable operator experience due to the imperfect effectiveness of CDTx, especially in patients with HR PE or comorbidities like malignancy. For example, our recent analysis of cancer-associated thrombosis demonstrated that oncological patients have similar in-hospital survival rates to non-oncological patients but worse long-term outcomes because of their underlying neoplastic disease [ 25 ]. Hence, our analysis is crucial to understand the factors associated with treatment outcomes and optimize future treatment decisions of PERT.…”
Section: Discussionmentioning
confidence: 99%
“…This might be associated with a lack of standardized algorithms to select patients for advanced PE therapies and variable operator experience due to the imperfect effectiveness of CDTx, especially in patients with HR PE or comorbidities like malignancy. For example, our recent analysis of cancer-associated thrombosis demonstrated that oncological patients have similar in-hospital CDT -catheter-directed thrombectomy; CDL -catheter-directed thrombolysis; CPR -cardiopulmonary resuscitation; F -female; ICD -implantable cardioverter-defibrillator; IVCf -inferior vena cava filter; M -male; N/A -not applicable; NYHA FC -New York Heart Association Functional Classification; PE -pulmonary embolism; PESI -Pulmonary Embolism Severity Index; sPESI -simplified PESI; SE -surgical embolectomy; ST -systemic thrombolysis; rtPA -recombinant tissue plasminogen activator survival rates to non-oncological patients but worse long-term outcomes because of their underlying neoplastic disease [25]. Hence, our analysis is crucial to understand the factors associated with treatment outcomes and optimize future treatment decisions of PERT.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical point of view, prompt diagnosis of pulmonary embolism appears to be the most important issue, as it is an acute disease requiring immediate initiation of anticoagulant therapy. Oncology patients may require consultation from the acute pulmonary embolism response team (PERT) due to the numerous contraindications to thrombolytic therapy [41]. For dasatinib-induced NP, the drug should be discontinued, and another TKI should be used.…”
Section: Practical Commentmentioning
confidence: 99%